Strategies for Digital Economy Operation of Urban Parks Guided by Gamification Methods - Zhaochen WANG (Fengjing Yuanlin, 2025)
ObjectiveIn the mid-to-late stages of China’s urbanization process, the high-quality development of existing urban areas has placed higher demands on the functions and benefits of park green spaces, making operations a new focus for the renewal and construction of urban parks. However, due to constraints such as construction scale, resource endowment, location and transportation, customer base, as well as external factors like public welfare attributes, funding sources, and policies, existing urban park operation strategies can hardly fully utilize the potential value of green spaces and achieve the ideal revenue capacity needed to support continuous park operation. The rise of sectors such as integrated transportation and tourism, and the low-altitude economy, highlights the opportunities that entertainment consumption and new technologies bring to the construction industry. As a dynamic form of the digital economy, video games are exerting a significant radiating effect on the consumer service and cultural tourism sectors. This research explores the use of gamification methods to provide new ideas for digital economy operation of urban parks, with a view to seizing these emerging opportunities and unlocking the diverse values of urban parks.MethodsThe positive value of games is gaining wider recognition and serving as an important cultural and artistic medium across more interdisciplinary fields. Game researchers have begun to use spaces like natural wilderness areas, archives, and art galleries as platforms for promoting the positive value of games. Urban parks also possess the potential to serve as carriers of the positive value of games. In game studies, landscape architecture has always been an important research subject, providing materials and support from perspectives such as art and landscape history. Gamification methods and related technologies have already been applied in various forms in the teaching, research, and new display media within the field of landscape architecture.ResultsLike landscape architecture, games carry leisure and recreational functions and profound cultural attributes, with their design and operation reflecting simulations of the real world. Based on these common characteristics, this research uses mainstream ontological thinking from game studies to establish a shared ontological model for both games and landscape architecture. The model includes three core elements: environment, people, and rules Using these elements as a framework, the research explores gamification applications in three aspects: design, service, and operation. The results identify three categories of methods: Interactive experience-oriented scene design, human-centered service based on co-creation relationships, and rules and operations for sustained revenue. These methods not only provide a conceptual framework for park operations but also offer support for other work related to urban parks. Based on this system of methods, an analogy and transfer approach is used to create a framework for the sustainable operation of gamified parks within the digital economy. This includes conservative and radical digital economy mode transfer approaches, value-added products and token systems, consumption service scenarios and event planning directions, as well as the construction of support and security systems.ConclusionThe gamification methods derived from ontological thinking in landscape architecture cover potential gamified application scenarios in the design, service, and operation domains of landscape architecture, complementing existing application areas and supporting the construction of a gamified digital economy operation system for parks. This system is expected to promote the exploration of diverse values, including economic, data, and cultural aspects of park green spaces, such as value-added development, revenue enhancement, data collection, and cultural exploration and display. However, the above methods and systems require broader practical verification and attention to risks related to over-commercialization and cultural censorship. Gamification methods can also help landscape architecture professionals explore new paths for industry transformation in terms of spatial limitations, identity constraints, and cooperation mechanisms. Green spaces can also leverage their open and shared attributes to become spaces for promoting positive game values and game literacy development. Relying on innovation in interdisciplinary fields, this approach can support the shift of the planning and construction industry from the “finite game” seeking incremental growth to the “infinite game” seeking continuous renewals.